Climate, Environment and Cree Observations James Bay Territory, Canada - Royer, Marie-Jeanne S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines the effects of climate and environmental change in the Eastern James Bay, Canada. This socio-environmentally oriented volume integrates scientific literature with the established ecological knowledge to explore current issues. This multidisciplinary approach allows for a broader understanding of the forces at play on the environment and the societies that inhabit it. It is suited to a wide range of readers from researchers and professionals working in the field to graduate students in climate change, geography, environmental science and ecology.
Keywords: Environment; Climate change; Atmospheric sciences; Environment; Climate Change; Climate Change/Climate Change Impacts; Atmospheric Sciences; Electronic books